Wastewater Refinery: Producing Multiple Valuable Outputs from Wastewater - Sigrid Kusch-Brandt; Mohammad A. T. Alsheyab (J, 2021)
A wastewater refinery is a multifunctional solution that combines different technologies and processing schemes to recover a spectrum of valuable materials from municipal or industrial wastewater. The concept of wastewater refinery introduces a new perspective on wastewater treatment and management. It aims at making the most of wastewater constituents by co-producing different worthful outputs, such as water, energy, nitrogen, sulfide, and phosphorous. This can turn the treatment of wastewater from a major cost into a source of profit. The wastewater refinery approach is well aligned with the concept of the circular economy. A case study on Qatar’s wastewater revealed the potential recovery of significant quantities of valuable resources embodied in the country’s wastewater. Valorization of organic constituents and the recovery of nitrogen, phosphorus, and sulfide should be given priority. To facilitate the adoption of the wastewater refinery concept, research is required to explore technical and economic bottlenecks.